KRITERIA PENENTUAN BANK PENERIMA SETORAN BIAYA PENYELENGGARAAN IBADAH HAJI - Ihtiar, Habib Waidatul (IAIN Tulungagung, 2017)
In order to facilitate the payment of hajj costs, the Indonesian government has appointed several banking institutions as the authorized receivers of the hajj costs. The banks hereinafter Receiver Bank of Hajj Cost Deposit (BPS-BPIH). The emergence of many banking institutions makes it easier for the Indonesian government in choosing the appropriate banks which become the authorized receiver of the hajj cost deposit. However, in determining the authorized banks the government sets certain criteria in order that the bank service can run well and in accordance with the objectives set out in the regulation.Keywords: Kriteria, Bank Penerima Setoran Biaya Penyelanggaraan Ibadah Haji